The ambivalent nature of the relationship between lymphatics and cancer - Choi, Joshua; Choi, Ellie; Choi, Dongwon (Frontiers in Cell and Developmental Biology, 2022)
Do lymphatic vessels support cancer cells? Or are they vessels that help suppress cancer development? It is known that the lymphatic system is a vehicle for tumor metastasis and that the lymphangiogenic regulator VEGF-C supports the tumor. One such role of VEGF-C is the suppression of the immune response to cancer. The lymphatic system has also been correlated with an increase in interstitial fluid pressure of the tumor microenvironment. On the other hand, lymphatic vessels facilitate immune surveillance to mount an immune response against tumors with the support of VEGF-C. Furthermore, the activation of lymphatic fluid drainage may prove to filter and decrease tumor interstitial fluid pressure. In this review, we provide an overview of the dynamic between lymphatics, cancer, and tumor fluid pressure to suggest that lymphatic vessels may be used as an antitumor therapy due to their capabilities of immune surveillance and fluid pressure drainage. The application of this potential may help to prevent tumor proliferation or increase the efficacy of drugs that target cancer.